New models of self-management education for minority ethnic groups: pilot randomized trial of a story-sharing intervention. - Greenhalgh, T; Campbell-Richards, D; Vijayaraghavan, S; Collard, A; Malik, F; Griffin, M; Morris, J; Claydon, A; Macfarlane, F (2011)
OBJECTIVE: no model of self-management education or peer support has yet achieved widespread reach and acceptability with minority ethnic groups. We sought to refine and test a new complex intervention in diabetes education: informal story-sharing groups facilitated by bilingual health advocates. METHODS: pilot randomized trial with in-depth process evaluation in a socioeconomically deprived area. 157 people referred for diabetes education were randomized by concealed allocation to an intervention (story-sharing group in their own language) or control ('usual care' self-management education, through an interpreter if necessary) arm. Story-sharing groups were held in five ethnic languages and English (for African Caribbeans), and ran fortnightly for six months. Primary outcome was UKPDS (UK Prospective Diabetes Study) risk score. Secondary outcomes included attendance, HbA1c, well-being and enablement. Process measures included ethnographic observation, and qualitative interviews with staff and patients. RESULTS: some follow-up data were obtained on 87% of participants. There was no significant difference between intervention and control arms in biomedical outcomes. Attendance was 79% in the story-sharing arm and 35% in the control arm (p < 0.0001), and patient enablement scores were significantly higher (8.3 compared to 5.9, p < 0.005). The model was very popular with clinicians, managers and patients, which helped overcome numerous challenges to its successful embedding in a busy public sector diabetes service. CONCLUSION: people from minority ethnic groups in a socioeconomically deprived area were keen to attend informal story-sharing groups and felt empowered by them, but clinical outcomes were no better than with conventional education. Further research is needed to maximize the potential and evaluate the place of this appealing service model before it is introduced as a part of mainstream diabetes services.